Omega-3 Polyunsaturated Fatty Acids Reduce the Incidence of Postoperative Atrial Fibrillation in Patients with History of Prior Myocardial Infarction Undergoing Isolated Coronary Artery Bypass Grafting - Wilbring, Manuel; Ploetze, Katrin; Bormann, Susann; Waldow, Thomas; Matschke, Klaus (The Thoracic and Cardiovascular Surgeon, 2014)
Introduction The impact of omega-3 polyunsaturated fatty acids (PUFAs) for prevention of atrial fibrillation (AF) is still part of a lively debate. The present study evaluates the impact of orally administered omega-3 ethyl ester concentrate (omega-3 PUFA) on postoperative onset of AF in patients with recent myocardial infarction (≤ 3 months) undergoing isolated coronary artery bypass grafting (CABG).Patients and Methods The study included a total of 198 patients with recent (≤ 3 months) myocardial infarction. The treatment group consisted of 99 prospectively and randomly assigned patients. A matched control group was generated out of the entirety of patients undergoing isolated CABG during the same time period, being not treated with omega-3 PUFA. Primary endpoint was onset of postoperative AF. Patients of the treatment group received a daily dose of 2 g omega-3 PUFA, initiated 5 days before surgery. Effective serum levels were confirmed by laboratory testing.Results Patients of the treatment group had less frequently postoperative AF (treatment: 31.3% vs. control: 48.0%; p = 0.017). The reduction in relative risk was 34.8% in the treatment group, which conforms a number needed to treat (NNT) of 6.0 patients. A more pronounced effect with a NNT of 4.1 was observed in patients ≤ 70 years (p = 0.007). Besides, patients of the treatment group had a shorter intensive care unit stay (p = 0.001) and suffered less frequently from impaired wound healing by trend (p = 0.063). One patient out of treatment group and two out of control group died during hospital stay (p = 1.000).Conclusion Preoperative administration of 2 g omega-3 PUFA reduces incidence of postoperative AF in patients with recent (≤ 3 months) myocardial infarction undergoing isolated CABG.
Keywords: Omacor; Omega-3; PUFA; CABG; atrial fibrillation